Phase transitions in octanethiol-capped Ag nanocluster microfilm assemblies - Ellis, A.; D'Arcy-Galla, J.; Vijayamohanan, K.; Goswami, R.; Ganesan, P. G.; Ryu, C.; Ramanath, G. (Thermochimica Acta, 2005)
We describe phase transitions in microfilm assemblies of octanethiol (OT)-capped 2-4 nm-diameter Ag nanoclusters prepared from solutions with OT/Ag+ ratios of similar to50. Using DSC we observe two melting/crystallization-type reversible phase transitions: one at similar to61 degreesC due to interdigiated unattached octanethiol, and the other at similar to125 degreesC due to the phase comprised of the assembly of OT-capped nanoclusters. Increased thermal fluctuations weaken the inter-chain hydrophobic interactions between interdigitated OT molecules, leading to both phase transitions. The thiolate bond of OT-molecules bound to Ag nanoclusters are more rigid, thereby requiring a higher temperature to increase the flexibility of the alkyl chain of OT, and to melt the nanocluster assembly. The mobility of the nanoclusters in the melt is limited, and morphological features of the original assemblies are retained during recrystallization. No observable mass loss is detected up to similar to180 degreesC, above which OT molecules desorb from the Ag nanoclusters. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: differential thermal analysis; infrared spectroscopy; phase transitions; silver nanoclusters